2009
DOI: 10.2139/ssrn.1470048
|View full text |Cite
|
Sign up to set email alerts
|

Piety and Profits: Stock Market Anomaly During the Muslim Holy Month

Abstract: --------------------------------------------------------------------------------------------------------------------Observed by more than 1.5 billion Muslims, Ramadan is one of the most celebrated religious rituals in the world. We investigate stock returns during Ramadan for 14 predominantly Muslim countries over the years [1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007]. The results show that stock returns during Ramadan are almost nine times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
(18 reference statements)
1
13
0
1
Order By: Relevance
“…Clingingsmith, Khwaja and Kremer (2009) show that identification with the global Muslim community may also strengthen following participation in the Hajj, but we lack individual Hajj participation data to test this conjecture in this context. Following Frieder and Subrahmanyam (2004), Bialkowski, Etebari and Wisniewski (2010) show that equity returns in 14 Muslim markets are substantially higher during Ramadan, while volatility is markedly lower (see also Bialkowski, Bohl, Kaufmann and Wisniewski (2013)). These findings can possibly be attributed to the sentiment of Islamic investors and their trades during this period.…”
Section: E Borrower Bank or Loan Characteristics? Or Religion?mentioning
confidence: 89%
“…Clingingsmith, Khwaja and Kremer (2009) show that identification with the global Muslim community may also strengthen following participation in the Hajj, but we lack individual Hajj participation data to test this conjecture in this context. Following Frieder and Subrahmanyam (2004), Bialkowski, Etebari and Wisniewski (2010) show that equity returns in 14 Muslim markets are substantially higher during Ramadan, while volatility is markedly lower (see also Bialkowski, Bohl, Kaufmann and Wisniewski (2013)). These findings can possibly be attributed to the sentiment of Islamic investors and their trades during this period.…”
Section: E Borrower Bank or Loan Characteristics? Or Religion?mentioning
confidence: 89%
“…However, the stocks were found less volatile in Rabi-ul-Awwal and Ramadan in KSE, and more volatile in Muharram and Shawwal in BSE. Alrashidi et al (2014) Bialkowski et al (2010) found positive investor valuation effect of Ramadan. Moreover, Al Rjoub (2010) concluded that daily stock returns during the first half of Ramadan is relatively higher than the second half of the month.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Hong and Yu (2009) confirm that the trading volume is lower during the summer because market participants are on holiday. However, Bialkowski, Etebari, and Wisniewski (2010) found higher stock returns and no change in the trading volume during Ramadan. However, Bialkowski, Etebari, and Wisniewski (2010) found higher stock returns and no change in the trading volume during Ramadan.…”
Section: Holiday Effectmentioning
confidence: 85%
“…Similarly, Al-Ississ (2010) reported significantly lower trading volume and changes in daily stock returns in 17 Muslim financial markets during the Muslim holy days of Ramadan and Ashoura. However, Bialkowski, Etebari, and Wisniewski (2010) found higher stock returns and no change in the trading volume during Ramadan.…”
Section: Holiday Effectmentioning
confidence: 85%